2022
DOI: 10.3389/fmicb.2022.993146
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate mediates histone crotonylation and alleviated neonatal rats hypoxic–ischemic brain injury through gut–brain axis

Abstract: Neonatal hypoxic–ischemic encephalopathy (HIE) refers to nervous system damage caused by perinatal hypoxia, which is the major cause of long-term neuro-developmental disorders in surviving infants. However, the mechanisms still require further investigation. In this study, we found that the butanoate metabolism pathway exhibited significantly decreased and short chain fatty acid (SCFAs)-producing bacteria, especially butyrate-producing bacteria, were significantly decreased in fecal of neonatal hypoxic–ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Reversely, the decreased abundance of Lachnospiraceae family is negatively associated with severity in other CNS diseases, such as depression and Parkinson [30,31]. Meanwhile, previous studies of hypoxic or ischemic-hypoxic brain injury have shown a decrease in the proportion of Firmicutes [5]. It's di cult to conclude they are protective or risk factor, because of Lachnospiraceae family and Butyricoccus genus as a member of the Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reversely, the decreased abundance of Lachnospiraceae family is negatively associated with severity in other CNS diseases, such as depression and Parkinson [30,31]. Meanwhile, previous studies of hypoxic or ischemic-hypoxic brain injury have shown a decrease in the proportion of Firmicutes [5]. It's di cult to conclude they are protective or risk factor, because of Lachnospiraceae family and Butyricoccus genus as a member of the Firmicutes.…”
Section: Discussionmentioning
confidence: 99%
“…Anoxic brain injury (ABI), such as traumatic brain injury [1], stroke [2], cardiac arrest [3], asphyxia [4] and neonatal ischemic hypoxic encephalopathy [5], is a common clinical cause of central nervous system (CNS) injury. It can occur in various age groups with poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained from Mass spectrometry in different samples were chromatographic peaks and the peak areas were integrated on all chromatographic peaks. The peak areas denotes the relevant metabolites (He et al, 2022).…”
Section: Targeted Metabolomic Analysismentioning
confidence: 99%
“…Mice experiments found that high dietary fiber intake improved cognitive and social behavioral deficits in the offspring of obese maternal mice by modulating the composition of the offspring's Clostridiales and Bacteroidales and SCFAs 125 . Moreover, sodium butyrate promoted the recovery of SCFA‐producing bacteria in neonatal rats with hypoxic–ischemic brain damage, facilitating the recovery of cerebral cortex and hippocampus 126 . However, not all fibers are beneficial; unfermented fibers may elicit the production of pro‐inflammatory factors by immune cells, activating the NLRP3 and TLR2 pathways and exacerbating inflammation in Inflammatory bowel disease (IBD) 127 .…”
Section: Treatment Of Brain Injury In Preterm Infants Mediated Throug...mentioning
confidence: 99%